2015
DOI: 10.1007/s13277-015-3835-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-211 promotes non-small cell lung cancer proliferation by targeting SRCIN1

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that, when dysregulated, are involved in the initiation and progression of various cancers, including lung cancer, in humans. In the current study, qRT-PCR was performed to measure miR-211 expression in human non-small cell lung cancer (NSCLC) cell lines and tissues. Cell proliferation, cell cycle, colony formation, and invasion were performed to detect the functional role of miR-211 in human NSCLC cell line. We used luciferase reporter assay to find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
(49 reference statements)
0
40
0
Order By: Relevance
“…Recent reports have underlined that p140Cap regulates proliferation and migration in colon, lung, gastric, cutaneous squamous carcinoma and osteosarcoma cancer cells192021222324. Indeed, in a cohort of breast cancer patients, p140Cap expression was linked to a less aggressive breast cancer disease25, leading to the hypothesis that in these tumours p140Cap may counteract tumour fitness.…”
mentioning
confidence: 99%
“…Recent reports have underlined that p140Cap regulates proliferation and migration in colon, lung, gastric, cutaneous squamous carcinoma and osteosarcoma cancer cells192021222324. Indeed, in a cohort of breast cancer patients, p140Cap expression was linked to a less aggressive breast cancer disease25, leading to the hypothesis that in these tumours p140Cap may counteract tumour fitness.…”
mentioning
confidence: 99%
“…Elucidation of the MALAT1/ miR-211/PHF19 pathway may contribute to the beginnings of a better understanding of OC pathogenesis, and the components of this pathway, MALAT1, miR-211, and PHF19, can be used as novel diagnostic and prognostic markers for clinical prevention and treatment of OC. miR-211 is abnormally expressed in a wide range of cancers and functions as a tumor-promoting gene or a tumor suppressor (16,(47)(48)(49)(50). Searching the literature, Xia et al (16) found that miR-211 arrests cells at the G0/G1 stage, suppresses cellular proliferation, and induces apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mir-211-3p differs among different cancers [27, 28]. Previous data have demonstrated miR-211-3p is an important oncogenic miRNA in CRC, which is significantly upregulated in CRC and high expression of miR-211-3p indicates poor survival [29].…”
Section: Discussionmentioning
confidence: 99%